Retrospective observational study of the association of peak blood glucose during the second 24 hours of admission with hospital-acquired complications in non-critical care admissions to a tertiary referral teaching hospital - Andrew Georgiou; Getiye Dejenu Kibret; Barbara Depczynski; Sue Mei Lau (BMJ Open)
Introduction Stress hyperglycaemia at hospital presentation is associated with poorer outcomes. Less is known about the risk of poorer outcomes according to achieved glycaemia early in the admission.Research design/methods This was a retrospective observational study of patients admitted to non-critical care wards. The aim was to determine the relationship between the day 2 peak blood glucose and the occurrence of hospital-acquired complications (HACs) or in-hospital mortality. A Cox proportional hazards model, adjusted for relevant covariates, was used to evaluate the impact of day 2 peak glucose on HACs and in-hospital mortality, and we identified peak glucose thresholds correlating with an increase in risk.Results For the whole cohort, day 2 peak glucose was associated with an increased risk of any HAC, aHR=1.06, 95% CI: 1.04, 1.07; but not in-hospital mortality, aHR=0.98, 95% CI: 0.94, 1.01. The risk of HAC infection increased by 4.6% for every mmol/L rise in day 2 peak glucose (aHR=1.05, 95% CI: 1.02, 1.08) in the diabetes cohort compared with 5.5% (aHR=1.06, 95% CI: 1.00, 1.11) in the non-diabetes cohort. The risk of HAC cardiac in the diabetes cohort increased by 5.3% (aHR=1.05, CI: 1.01, 1.10) per mmol/L increase in day 2 peak glucose; no association was found in the non-diabetes cohort (aHR=1.03, 95% CI: 0.94, 1.13). The risk for in-hospital mortality was associated with day 2 peak glucose, aHR=1.11, 95% CI: 1.03, 1.20, in patients without diabetes, but not in patients with diabetes, aHR=1.00, 95% CI: 0.95, 1.06. There was an increase in the risk of HAC once day 2 peak blood glucose exceeded 19.0 mmol/L (whole cohort), with thresholds of 13.6 mmol/L in the non-diabetes group and 19.5 mmol/L in the diabetes group.Conclusion The peak glucose on day 2 was a predictor of HAC in the entire cohort and in-hospital mortality in patients without diabetes.